Diagnostic Value of Quantitative Analysis by Contrast‐Enhanced Ultrasound of Endometrial Lesions. (15th September 2020) - Xu, Jia; Qiao, Lang; Xiong, Kailing; Cheng, Shutao; Luo, Hong; Wang, Yang; He, Junxuan; Chen, Xin; Pan, Mei
Abstract : Objectives: To explore the diagnostic value of time‐intensity curve parameters from contrast‐enhanced ultrasound (CEUS) examinations of endometrial lesions. Methods: Fifty‐two patients with suspected endometrial lesions who received vaginal CEUS examinations were divided into a polyp group (n = 36), a malignant group (n = 11), and a normal control group (n = 5) based on the pathologic diagnosis. The midpoint of the myometrium at the same depth as the endometrial lesion was used as the reference point. The initial increase time, time to peak, area under the curve, and peak intensity were determined by the time‐intensity curve. The relative parameters, namely, the initial increase time difference, peak time difference, area ratio, and peak intensity ratio, were also calculated and analyzed statistically. Results: The comparison results of the relative parameters among the groups showed that the differences in the time difference, intensity ratio, and area ratio were statistically significant. The differences in the intensity ratio and time difference between the malignant and normal groups were statistically significant ( P  < .001). The differences in the intensity ratio, area ratio, and time difference between the malignant and polyp groups were statistically significant ( P  < .001). The diagnostic value of the intensity ratio and area ratio was confirmed by a receiver operating characteristic curve. The sensitivity and specificity of the intensity ratio and area ratio in the groups were 100% and 77.5% and 85.7% and 85.0%, respectively. Conclusions: The relative CEUS parameters in endometrial lesions provide more diagnostic value in differential diagnosis of benign and malignant lesions than the absolute parameters.